Arrested in Glass: Actin within Sophisticated Architectures of Biosilica in Sponges. Issue 11 (13th February 2022) - Ehrlich, Hermann; Luczak, Magdalena; Ziganshin, Rustam; Mikšík, Ivan; Wysokowski, Marcin; Simon, Paul; Baranowska‐Bosiacka, Irena; Kupnicka, Patrycja; Ereskovsky, Alexander; Galli, Roberta; Dyshlovoy, Sergey; Fischer, Jonas; et al.
Abstract: Actin is a fundamental member of an ancient superfamily of structural intracellular proteins and plays a crucial role in cytoskeleton dynamics, ciliogenesis, phagocytosis, and force generation in both prokaryotes and eukaryotes. It is shown that actin has another function in metazoans: patterning biosilica deposition, a role that has spanned over 500 million years. Species of glass sponges (Hexactinellida) and demosponges (Demospongiae), representatives of the first metazoans, with a broad diversity of skeletal structures with hierarchical architecture unchanged since the late Precambrian, are studied. By etching their skeletons, organic templates dominated by individual F‐actin filaments, including branched fibers and the longest, thickest actin fiber bundles ever reported, are isolated. It is proposed that these actin‐rich filaments are not the primary site of biosilicification, but this highly sophisticated and multi‐scale form of biomineralization in metazoans is ptterned. Abstract : This work provides an answer to one of the fundamental questions of science, namely, why biological glass grows past at ambient temperatures and reaches dimensions in the meter range. It is shown that actin has a new function in metazoans: patterning highly sophisticated biosilica deposition in sponges that has spanned over 500 million years.